2018
DOI: 10.1111/trf.14460
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus RNA polymerase chain reaction on the utility channel of a commercial nucleic acid testing system

Abstract: We developed a sensitive ZIKV PCR assay on the cobas omni UC on the cobas 6800 system. The assay can be used for large-scale screening of blood donations for ZIKV or for testing of blood donors returning from areas with ZIKV to avoid temporal deferral. This study also demonstrates that the cobas omni UC on the cobas 6800 system can be used for in-house-developed PCR assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The system used in this study fully automates nucleic acid extraction, purification, amplification and detection. We, among others, have previously demonstrated that laboratory-developed tests can be adapted for fully automated PCR platforms such as the cobas 6800 system [6,13]. After brief preparation, clinical samples can be loaded directly into the device; required hands-on time and manual steps are reduced by up to 60% (manual steps reduced from 33 to 14, hands-on time reduced from 74 min to 14 min) compared with Dark blue curves: specific SARS-CoV-2 signals of IVT-RNA at 100,000 copies/mL (1), 10,000 copies/ml (2), 1,000 copies/ml (3) and 100 copies/ml (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system used in this study fully automates nucleic acid extraction, purification, amplification and detection. We, among others, have previously demonstrated that laboratory-developed tests can be adapted for fully automated PCR platforms such as the cobas 6800 system [6,13]. After brief preparation, clinical samples can be loaded directly into the device; required hands-on time and manual steps are reduced by up to 60% (manual steps reduced from 33 to 14, hands-on time reduced from 74 min to 14 min) compared with Dark blue curves: specific SARS-CoV-2 signals of IVT-RNA at 100,000 copies/mL (1), 10,000 copies/ml (2), 1,000 copies/ml (3) and 100 copies/ml (4).…”
Section: Discussionmentioning
confidence: 99%
“…After mixing, the 6 mL are transferred to the reagent cassette. The Mmx cassette is delivered with a full-process control: it is preloaded with an internal control (IC) RNA together with primers and probe of the IC detection assay by default [6]. Instrument settings in the cobas mni Utility Channel software (Roche, Los Gatos, US) and the temperature profile used for the RT-PCR reaction are summarised in Table 1.…”
Section: Sars-cov-2 Utility Channel Test Setupmentioning
confidence: 99%
“…Commercial nucleic acid testing devices for detection [217][218][219][220].Such as the instrument-free, disposable PCR testing kit developed by Visby Medical Inc, which allows for on-demand testing with rapid results [221]. Although currently authorized for laboratory testing, their device simplifies the testing process by collecting a sample and placing it in The fully automated and enclosed nature of the extraction, amplification, and detection processes significantly reduces testing time and improves testing efficiency.…”
Section: Commercial Nucleic Acid Testing Equipmentmentioning
confidence: 99%